A new molecular method for the rapid subtyping of bovine herpesvirus 1 field isolates - Maidana, Silvina Soledad; Miño, Samuel; Apostolo, Romina Maria; De Stefano, Gabriel Alejandro; Romera, Sonia Alejandra (Sage Publications, 2020)
Bovine herpesvirus 1 (BoHV-1) causes several clinical syndromes in cattle worldwide. There are 3 subtypes of BoHV-1: 1.1, 1.2a, and 1.2b. Several molecular methods are commonly used in the detection and characterization of BoHV-1. Among them, restriction endonuclease analysis (REA) and single-nucleotide polymorphism (SNP) analysis of the complete viral genome allow classification of BoHV-1 into different subtypes. However, developing countries need simpler and cheaper screening assays for routine testing. We designed a standard multiplex PCR followed by a REA assay allowing straightforward subclassification of all BoHV-1 isolates tested into 1.1, 1.2a, and 1.2b subtypes based on the analysis of fragment length polymorphism. Our standard multiplex PCR-REA was used to analyze 33 field strains of BoHV-1 isolated from various tissues. The assay confirmed the subtype identified previously by REA. In addition, non-polymorphic or undigested fragments were sequenced in order to confirm the mutation affecting the RE HindIII site. Our PCR-REA method is an affordable and rapid test that will subtype all BoHV-1 strains.